TNF-α Gene Promoter -238G>A and -308G>A Polymorphisms Alter Risk of Psoriasis Vulgaris: A Meta-Analysis - Li, Chunying; Wang, Gang; Gao, Ying; Liu, Ling; Gao, Tianwen (Journal of investigative dermatology, 2007)
Tumor necrosis factor-α (TNF-α) is a major proinflammatory cytokine and involved in the etiology of psoriasis. The -238G>A and -308G>A polymorphisms influence the transcription of the TNF-α gene and have been implicated in psoriasis risk. However, the results from the published studies on the association between TNF-α polymorphisms and psoriasis risk are conflicting. Our meta-analysis of a total of 997 psoriasis cases and 943 control subjects from eight published case–control studies for the -238G>A polymorphism and of 1,156 psoriasis cases and 1,083 control subjects from 10 published case–control studies for the -308G>A polymorphism showed that a significantly increased risk was associated with the variant GA+AA genotypes of -238G>A, compared with the GG genotype (odds ratio (OR) 2.60, 95% confidence interval (95% CI) 1.48–4.56), whereas a significantly reduced psoriasis risk was associated with the variant GA+AA genotypes of the -308G>A compared with the GG genotype (OR 0.57, 95% CI 0.45–0.71). Our findings suggest that TNF-α -238G>A and -308G>A polymorphisms might be used as biomarkers for psoriasis risk prediction. A single larger study with thousands of subjects and biochemical and biological characterization is warranted to evaluate further the role of -238G>A and -308G>A polymorphisms and psoriasis risk in a population of various ethnicities.